2012
DOI: 10.1007/s00595-012-0186-9
|View full text |Cite
|
Sign up to set email alerts
|

Occult papillary thyroid microcarcinoma manifesting only as a symptomatic lateral cervical mass: report of a case

Abstract: We report a case of occult papillary thyroid carcinoma (PTC) manifesting as a solitary lateral cervical mass. Few such cases have been reported and, to our knowledge, this is the first report of cervical lymph node involvement from thyroid cancer being so massive that it is the cause of the local symptoms. The patient, a 64-year-old man, presented with vocal cord paralysis and voice alteration and was found to have a 4 cm lateral cervical mass infiltrating the ipsilateral internal jugular vein and recurrent la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Batori et al reported a case of a patient who had presented with a cervical mass for 15 months, but had already suffered from dysphagia and dysphonia despite a mere diameter of 5 cm. [3] Therefore, it appears that size and duration of the mass alone do not essentially correspond to its debilitating potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Batori et al reported a case of a patient who had presented with a cervical mass for 15 months, but had already suffered from dysphagia and dysphonia despite a mere diameter of 5 cm. [3] Therefore, it appears that size and duration of the mass alone do not essentially correspond to its debilitating potential.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] However, mere microscopic evaluation of fine-needle aspirates might not be sufficient for adequate diagnosis since they are commonly false negative. [3] Instead, thyroglobulin measurements in the specimen have been proven helpful for accurate diagnosis of cystic lesions as thyroid metastases. [2]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTC is characterized by slow growth and indolent biological behavior, but with frequent cervical lymph node metastases. By the time of diagnosis PTC has already spread to cervical lymph nodes in 20% -50% of patients [6] [7].…”
Section: Introductionmentioning
confidence: 99%